O impacto psicológico das cardiopatias no paciente e em seus cuidadores - Bley, Angela de Leão (2015)
This investigation intends to study, to analyze, and to discuss the psychological impact of cardiopaty on patients and health care supporters as well as behavior and emotional strategies on pediatric cardiopaties at Pequeno Príncipe Hospital in Curitiba. It is necessary to deepen contempts concerning the heart and to point out medical activities that, after all, work together with the psychological staff that deals, not only with the patient, but also with this patient s siblings. Besides, this research stands for the need of working with protection factors which may increase a resilient attitude towards facing this hard situation which eventually may help this group with some psychological deeds. The methodology used is that of a quantity and a qualifying research, with the use of field researches, interviews, comparative analyzes, charts, and with the necessary support of a major bibliography. This thesis is divided in nine chapters: the first of all deals with this organ named heart; the second works with the symbolic meaning of this very heart; chapter 4 studies infant up to adolescent developing steps; chapter 5 talks on resilience, facing the situation issues, and infant s and juvenile s quality of life. Chapter 6 shows the method of this study; chapter 7 points out the outcome of samples, charts, graphics, and the hypothesis shown during this investigations; chapter 8 studies the psychological impacts on groups that carry cardiopaty out. And last of all proposes a discussion on the studied issues in order to point out the relevance of this research. Thus, in intention here is to contribute for more effective psychological strategies in pediatric treatment concerning heart disease